Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1586/14737140.7.3.383
|View full text |Cite
|
Sign up to set email alerts
|

Urothelial carcinoma in the prostatic urethra and prostate: current controversies

Abstract: We reviewed the literature on urothelial carcinoma in the prostatic urethra and prostate. We concluded that the incidence of urothelial carcinoma in the prostatic urethra and prostate is probably underestimated. This fact warrants thorough follow-up of patients with high-risk bladder cancers and also whole-mount examination of the prostate after cystectomy to recognize the true incidence and extent of such tumor involvement. Resectoscope loop biopsy is the method of choice to detect urothelial carcinoma in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 43 publications
(57 reference statements)
0
16
0
Order By: Relevance
“…Some studies described invasive urothelial carcinoma or adenocarcinoma in the prostate specimens being found after radical cystoprostatectomy so that prostate-sparing surgery might not be performed in some circumstances [11, 12]. Yang et al even reported up to 53% incidental prostatic adenocarcinoma or urothelial carcinoma invasions in Chinese patients undergoing radical cystoprostatectomy [13].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies described invasive urothelial carcinoma or adenocarcinoma in the prostate specimens being found after radical cystoprostatectomy so that prostate-sparing surgery might not be performed in some circumstances [11, 12]. Yang et al even reported up to 53% incidental prostatic adenocarcinoma or urothelial carcinoma invasions in Chinese patients undergoing radical cystoprostatectomy [13].…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13] Previously described challenges in the reporting of bladder cancer include evaluating muscularis propria invasion, soft tissue margins, lymphovascular invasion, and lymph node status. [2][3][4][5][6][7][8][9][10][11][12][13] Previously described challenges in the reporting of bladder cancer include evaluating muscularis propria invasion, soft tissue margins, lymphovascular invasion, and lymph node status.…”
Section: Discussionmentioning
confidence: 99%
“…1 The published incidence of concomitant UC of the bladder and prostate or prostatic urethra in cystectomy series ranges from 10% to 48%. 2,14,15 In regards to treatment, the extent of prostatic involvement impacts the various modalities offered to patients. 2,14,15 In regards to treatment, the extent of prostatic involvement impacts the various modalities offered to patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extension of UC in the PU is certainly underestimated [8], although it has significant prognostic importance. Direct extension of UC into the prostate has the worst prognosis as is reflected by the WHO 2004 classification, which stages these tumors as pT4.…”
Section: Discussionmentioning
confidence: 99%